Antireflection glass and method for manufacturing the same
Patent Information
- Application Number
- CN202410456442.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-16
AI Technical Summary
[0006]现有光伏玻璃镀膜所用的双层镀膜,具有效率高达每分钟11平方,成本低显著优势,常用1.30-1.35和1.44-1.48的双层减反增透镀膜液和工艺对显示屏领域来说,反射率可低于1.2,但是耐磨远远不如超硬AR涂层
[0029]采用上述技术方案后,本发明与背景技术相比,具有如下优点:本发明制备的增透减反射玻璃中,M层增透减反射涂层、H层增透减反射涂层和L层增透减反射涂层的膜厚均为60-200nm,低于60nm不好精准控制膜厚,高于200nm,不利于产生光学干涉效果;光学玻璃没有涂覆涂层前,反射率为4%,光学玻璃涂覆本发明的M层镀膜液、H层镀膜液和L层镀膜液后,经固化,制得的增透减反射玻璃的反射率降低到0.8%,可实现对光的增透减反射效果;本发明采用溶胶凝胶镀膜,除了保持耐磨、耐化学性能好,耐光老化、耐候性好等特点外,与传统磁控溅射和PVD镀膜相比,具有生产效率高,可以做大尺寸,可以做异型件等显著优势。此外,最显著的特征是,涂层经高温固化后,可以耐硝酸钾420度以上180分钟的化学钢化不被破坏。
Smart Images

Figure CN118206295B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional glass technology, specifically relating to an anti-reflective glass and its preparation method. Background Technology
[0002] With the significant drop in price, displays, especially LCD displays, are now ubiquitous in our lives, found in mobile phones, tablets, laptops, televisions, and other specialized displays.
[0003] Since the surface of an LCD screen is mainly made of two materials, cellulose triacetate and glass, when the eyes look at the screen, ambient stray light enters the eyes along with the light from the screen image. To reduce the impact of ambient stray light on the display effect, there are generally four methods to reduce screen glare: micron-level anti-glare (AG), multi-layer optical structure anti-reflective coating (AR), moth-eye micro / nano structures, and nanospheres can reduce glare interference.
[0004] Because AG (anti-reflective coating) processes particles with diameters in the micrometer range, haze can easily cause flash points. Therefore, in the field of high-definition displays, multi-layer optical structure anti-reflective coatings (AR) have a significant advantage for high-resolution image display.
[0005] Antireflective coatings (AR) are typically achieved through methods such as vacuum evaporation (PVD), magnetron sputtering, and liquid roll coating or application. PVD coatings generally have poor adhesion and abrasion resistance to glass. In the display industry, magnetron sputtering is commonly used to create ultra-hard AR coatings, achieving reflectivity of <1.0%.
[0006] The existing double-layer coating used in photovoltaic glass coating has the advantages of high efficiency of up to 11 square meters per minute and low cost. The commonly used double-layer anti-reflective and anti-reflective coating solutions and processes of 1.30-1.35 and 1.44-1.48 can achieve a reflectivity of less than 1.2 for the display screen field, but the wear resistance is far inferior to that of the ultra-hard AR coating.
[0007] Using magnetron sputtering to create an ultra-hard AR coating on a display screen is very expensive due to the high cost of the production equipment, low production capacity (medium-sized equipment can only produce 30 12-inch glass cover plates per hour), and low yield rate. Only a few manufacturers can use it.
[0008] However, applying an antireflective coating (AR) to glass using a dip-coating process also presents significant problems. The biggest issue is that if chemically tempered glass is used for dip-coating, the difference in solvent evaporation rates between the edges and the center during the process creates a thickness difference, resulting in a thicker coating around the edges and a thinner coating in the center. This leads to a noticeable color difference between the edges and the center, and these areas are considered ineffective edges. If the substrate is plastic, these ineffective edges can be removed mechanically. However, for chemically tempered glass, mechanical or laser processing methods are inefficient and costly. More importantly, they reduce the impact resistance of the tempered glass.
[0009] Therefore, if a coating that can withstand chemical tempering can be developed, the coating process can be applied to the untempered glass first, and then the ineffective edges can be removed by mechanical processing, followed by edge grinding and polishing before chemical tempering. This would achieve both low-cost and high-efficiency AR processing and ensure that the impact resistance of the glass is maintained. Summary of the Invention
[0010] To address the above problems, this invention provides an anti-reflective glass and a method for preparing the same.
[0011] The present invention adopts the following technical solution:
[0012] A method for preparing antireflective and anti-reflective glass specifically includes the following steps:
[0013] S1. Mix nano-titanium dioxide sol, silane coupling agent, water, acid catalyst and alcohol solvent evenly, and let it mature at 25-80℃ for 4-48 hours. Then prepare H layer coating solution with solid content of 3.0-8.0%, and accurately measure the refractive index and solid content of H layer coating solution.
[0014] S2. Mix silica sol, silane coupling agent, water, acid catalyst and alcohol solvent evenly, and let it mature at 25-80℃ for 4-48 hours. Then prepare an L-layer coating solution with a solid content of 3.0-8.0%, and accurately measure the refractive index and solid content of the L-layer coating solution.
[0015] S3. Perform optical film system design, and use optical film system design software to calculate the required refractive index and thickness of each layer of the MHL film system;
[0016] S4. Based on the required refractive index of the M-layer coating solution, the required refractive index of the M-layer coating solution is obtained by compounding the H-layer coating solution and the L-layer coating solution. Prepare an M-layer coating solution with a solid content of 3.0-8.0%, and then accurately measure the refractive index and solid content of the M-layer coating solution.
[0017] S5. Based on the required thickness of the dip coating, fix the range of lifting speed and accurately adjust the required solid content of the M layer coating solution, H layer coating solution and L layer coating solution twice respectively.
[0018] S6. Apply the required thickness of M layer coating liquid to the optical glass, then allow it to dry to the surface, then pre-cur it, and then cool it to room temperature; then apply the required thickness of H layer coating liquid, then allow it to dry to the surface, then pre-cur it, and then cool it to room temperature; finally apply the required thickness of L layer coating liquid, then allow it to dry to the surface, and then pre-cur it.
[0019] S7. Place the pre-cured optical glass into a high-temperature oven for curing to obtain anti-reflective glass.
[0020] Preferably, step S7 is followed by step S8. The specific process of step S8 is to perform CNC machining on the coated antireflective glass according to the drawing to remove invalid edges or grind the edges, and then put it into a potassium nitrate chemical tempering furnace for tempering treatment.
[0021] Preferably, the silane coupling agent in steps S1 and S2 is one or more of Y-R1-Si(OR2)3, Si(OR2)3, or Si(OR2)4, wherein Y is an organic functional group, OR2 is a silaneoxy group, and R1 is methyl, ethyl, propyl, isopropyl, or butyl.
[0022] Preferably, the initial solid content of the H-layer coating solution, L-layer coating solution, and M-layer coating solution in steps S1, S2, and S4 is 3-8%, and the viscosity of the H-layer coating solution, L-layer coating solution, and M-layer coating solution is 1.0-4.0 cp.
[0023] Preferably, the specific process of step S6 is as follows: coating the optical glass with a coating liquid of the required thickness M layer, then surface drying at 50-80℃ for 3-15 minutes, then pre-curing at 100-200℃ for 3-15 minutes, and then cooling to room temperature; then coating the optical glass with a coating liquid of the required thickness H layer, then surface drying at 50-80℃ for 3-10 minutes, then pre-curing at 100-200℃ for 3-15 minutes, and then cooling to room temperature; finally coating the optical glass with a coating liquid of the required thickness L layer, surface drying at 50-80℃ for 3-15 minutes, and then pre-curing at 100-200℃ for 3-15 minutes.
[0024] Preferably, in the antireflective glass cured in step S7, the thickness of the M-layer antireflective coating, the H-layer antireflective coating, and the L-layer antireflective coating is 60-200 nm.
[0025] Preferably, in the antireflective glass cured in step S7, the refractive index of the M layer antireflective coating is 1.60-1.80, and the film thickness is 60-120 nm; the refractive index of the H layer antireflective coating is 1.80-2.10, and the film thickness is 60-120 nm; and the refractive index of the L layer antireflective coating is 1.30-1.50, and the film thickness is 60-200 nm.
[0026] Preferably, the curing temperature in step S7 is 200-600℃, and the curing time is 10-180 minutes.
[0027] An anti-reflective glass is prepared using the aforementioned method for preparing anti-reflective glass.
[0028] From the above schemes, a better solution can be obtained. The antireflective glass employs four layers of coating liquid: L-layer, M-layer, H-layer, and L-layer. Simulation using optical film system design software shows that this achieves better optical performance than the MHL three-layer design. Using six or eight even-numbered layers, or five, seven, or even more odd-numbered layers, the optical performance can surpass that of four or three-layer designs. The difference lies in the fact that more coating layers result in better optical performance, but also lower yield and higher cost. In the industrialization stage, it is necessary to rationally design and adopt the aforementioned three-, four-, five-layer, or other multi-layer coating structures based on optical performance and cost structure.
[0029] After adopting the above technical solution, the present invention has the following advantages compared with the prior art: In the antireflection and anti-reflection glass prepared by the present invention, the film thickness of the M-layer antireflection and anti-reflection coating, the H-layer antireflection and anti-reflection coating, and the L-layer antireflection and anti-reflection coating are all 60-200nm. If the film thickness is less than 60nm, it is difficult to accurately control the film thickness; if it is greater than 200nm, it is not conducive to producing optical interference effect. Before the optical glass is coated, the reflectivity is 4%. After the optical glass is coated with the M-layer coating solution, the H-layer coating solution, and the L-layer coating solution of the present invention, and cured, the reflectivity of the obtained antireflection and anti-reflection glass is reduced to 0.8%, which can achieve the effect of antireflection and anti-reflection of light. The present invention uses sol-gel coating, which, in addition to maintaining good wear resistance, chemical resistance, light aging resistance, and weather resistance, has significant advantages over traditional magnetron sputtering and PVD coating, such as high production efficiency, large size, and the ability to make irregular parts. Furthermore, the most significant feature is that, after high-temperature curing, the coating can withstand chemical tempering with potassium nitrate at temperatures above 420 degrees Celsius for 180 minutes without being damaged. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the structure of the antireflective and anti-reflective glass prepared according to the present invention;
[0031] Figure 2A comparison of the reflectivity curves of the antireflective glass prepared according to this invention and ordinary glass;
[0032] Figure 3 This is a comparison of the transmittance curves of the antireflective glass prepared according to the present invention and ordinary glass. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0034] See Figures 1 to 3 .
[0035] A method for preparing antireflective and anti-reflective glass specifically includes the following steps:
[0036] S1. Mix nano-titanium dioxide sol, silane coupling agent, water, acid catalyst and alcohol solvent evenly, and let it mature at 25-80℃ for 4-48 hours. Then prepare H layer coating solution with solid content of 3.0-8.0%, and accurately measure the refractive index and solid content of H layer coating solution.
[0037] S2. Mix silica sol, silane coupling agent, water, acid catalyst and alcohol solvent evenly, and let it mature at 25-80℃ for 4-48 hours. Then prepare an L-layer coating solution with a solid content of 3.0-8.0%, and accurately measure the refractive index and solid content of the L-layer coating solution.
[0038] S3. Perform optical film system design, and use optical film system design software to calculate the required refractive index and thickness of each layer of the MHL film system;
[0039] S4. Based on the required refractive index of the M-layer coating solution, the required refractive index of the M-layer coating solution is obtained by compounding the H-layer coating solution and the L-layer coating solution. Prepare an M-layer coating solution with a solid content of 3.0-8.0%, and then accurately measure the refractive index and solid content of the M-layer coating solution.
[0040] S5. Based on the required thickness of the dip coating, fix the lifting speed and accurately adjust the required solid content of the M layer coating solution, H layer coating solution and L layer coating solution twice respectively.
[0041] S6. Apply the required thickness of M layer coating liquid to the optical glass, then allow it to dry to the surface, then pre-cur it, and then cool it to room temperature; then apply the required thickness of H layer coating liquid, then allow it to dry to the surface, then pre-cur it, and then cool it to room temperature; finally apply the required thickness of L layer coating liquid, then allow it to dry to the surface, and then pre-cur it.
[0042] S7. Place the pre-cured optical glass into a high-temperature oven for curing to obtain anti-reflective glass.
[0043] Step S7 is followed by step S8. The specific process of step S8 is to CNC machine the coated antireflective glass according to the drawing to remove invalid edges or grind the edges, and then put it into a potassium nitrate chemical tempering furnace for tempering treatment.
[0044] The silane coupling agent mentioned in steps S1 and S2 is one or more of Y-R1-Si(OR2)3, Si(OR2)3, or Si(OR2)4, wherein Y is an organic functional group, OR2 is a silaneoxy group, and R1 is methyl, ethyl, propyl, isopropyl, or butyl.
[0045] The initial solid content of the H-layer coating solution, L-layer coating solution, and M-layer coating solution mentioned in steps S1, S2, and S4 is 3-8%, and the viscosity of the H-layer coating solution, L-layer coating solution, and M-layer coating solution is 1.0-4.0 cp.
[0046] The specific process of step S6 is as follows: apply the required thickness of M layer coating liquid to the optical glass, then surface dry at 50-80℃ for 3-15 minutes, then pre-cur at 100-200℃ for 3-15 minutes, and then cool to room temperature; then apply the required thickness of H layer coating liquid, then surface dry at 50-80℃ for 3-10 minutes, then pre-cur at 100-200℃ for 3-15 minutes, and then cool to room temperature; finally apply the required thickness of L layer coating liquid, surface dry at 50-80℃ for 3-15 minutes, and then pre-cur at 100-200℃ for 3-15 minutes.
[0047] In the antireflective glass cured in step S7, the thickness of the M-layer antireflective coating, H-layer antireflective coating, and L-layer antireflective coating is 60-200 nm.
[0048] In the antireflective glass cured in step S7, the refractive index of the M layer antireflective coating is 1.60-1.80, and the film thickness is 60-120 nm; the refractive index of the H layer antireflective coating is 1.80-2.10, and the film thickness is 60-120 nm; the refractive index of the L layer antireflective coating is 1.30-1.50, and the film thickness is 60-200 nm.
[0049] The curing temperature in step S7 is 200-600℃, and the curing time is 10-180 minutes.
[0050] A comparison of the reflectance curves of the antireflective glass prepared by this invention and ordinary glass is shown below. Figure 2 As shown, the transmittance curves of the antireflective glass prepared by this invention and ordinary glass are compared as follows: Figure 3 As shown.
[0051] An antireflective glass is prepared using the aforementioned method for preparing antireflective glass.
[0052] The antireflective glass contains at least one layer of each of the M-layer, H-layer, and L-layer antireflective coatings. That is, the number of antireflective coating layers in the glass can be three, four, five, six, etc. For example, when there are four layers, from the inside out, they can be optical glass, L-layer antireflective coating, M-layer antireflective coating, H-layer antireflective coating, and L-layer antireflective coating. The refractive index and film thickness of each layer can be obtained using optical film system design software. By flexibly adjusting step S6, the thickness, refractive index, and optical effect of the film system design can be achieved. Due to space limitations, not all examples are provided.
[0053] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing anti-reflective and anti-transmittance glass, characterized in that, Specifically, the following steps are included: S1. Mix nano-titanium dioxide sol, silane coupling agent, water, acid catalyst and alcohol solvent evenly, and let it mature at 25-80℃ for 4-48 hours. Then prepare H layer coating solution with solid content of 3.0-8.0%, and accurately measure the refractive index and solid content of H layer coating solution. S2. Mix silica sol, silane coupling agent, water, acid catalyst and alcohol solvent evenly, and let it mature at 25-80℃ for 4-48 hours. Then prepare an L-layer coating solution with a solid content of 3.0-8.0%, and accurately measure the refractive index and solid content of the L-layer coating solution. The silane coupling agent mentioned in steps S1 and S2 is one or more of Y-R1-Si(OR2)3 or Si(OR2)4, wherein Y is an organic functional group, OR2 is a silanoxy group, and R1 is methyl, ethyl, propyl, isopropyl or butyl. S3. Perform optical film system design, and use optical film system design software to calculate the required refractive index and thickness of each layer of the MHL film system; S4. Based on the required refractive index of the M-layer coating solution, the required refractive index of the M-layer coating solution is obtained by compounding the H-layer coating solution and the L-layer coating solution. Prepare an M-layer coating solution with a solid content of 3.0-8.0%, and then accurately measure the refractive index and solid content of the M-layer coating solution. S5. Based on the required thickness of the dip coating, fix the range of lifting speed and accurately adjust the required solid content of the M layer coating solution, H layer coating solution and L layer coating solution twice respectively. S6. Apply the required thickness of M layer coating liquid to the optical glass, then allow it to dry to the surface, then pre-cur it, and then cool it to room temperature; then apply the required thickness of H layer coating liquid, then allow it to dry to the surface, then pre-cur it, and then cool it to room temperature; finally apply the required thickness of L layer coating liquid, then allow it to dry to the surface, and then pre-cur it. The specific process of step S6 is as follows: Apply the required thickness of the M layer coating liquid to the optical glass, then surface dry at 50-80℃ for 3-15 minutes, then pre-cur at 100-200℃ for 3-15 minutes, and then cool to room temperature; then apply the required thickness of the H layer coating liquid, then surface dry at 50-80℃ for 3-10 minutes, then pre-cur at 100-200℃ for 3-15 minutes, and then cool to room temperature; finally apply the required thickness of the L layer coating liquid, surface dry at 50-80℃ for 3-15 minutes, and then pre-cur at 100-200℃ for 3-15 minutes. S7. Place the pre-cured optical glass into a high-temperature oven for curing to obtain anti-reflective glass. S8. After removing invalid edges or grinding the coated antireflective glass according to the drawings using CNC machining, it is then put into a potassium nitrate chemical tempering furnace for tempering treatment.
2. The method for preparing an antireflective glass as described in claim 1, characterized in that: The initial solid content of the H-layer coating solution, L-layer coating solution, and M-layer coating solution mentioned in steps S1, S2, and S4 is 3-8%, and the viscosity of the H-layer coating solution, L-layer coating solution, and M-layer coating solution is 1.0-4.0 cp.
3. The method for preparing an antireflective glass as described in claim 1, characterized in that: In step S7, the thickness of the antireflective coatings M, H, and L layers in the cured antireflective glass is 60-200 nm.
4. The method for preparing an antireflective glass as described in claim 1, characterized in that: In the antireflective glass cured in step S7, the refractive index of the M layer antireflective coating is 1.60-1.80, and the film thickness is 60-120 nm; the refractive index of the H layer antireflective coating is 1.80-2.10, and the film thickness is 60-120 nm; the refractive index of the L layer antireflective coating is 1.30-1.50, and the film thickness is 60-200 nm.
5. The method for preparing an antireflective glass as described in claim 1, characterized in that: The curing temperature in step S7 is 200-600℃, and the curing time is 10-180 minutes.
6. An anti-reflective glass, characterized in that: It is prepared using the method for preparing antireflective and anti-reflective glass as described in any one of claims 1-5.
Citation Information
Patent Citations
Method for producing antireflection reinforced glass
CN102574735A
Preparation method of anti-reflection film
CN107902918A